Rickettsia parkeri (Rickettsiales: Rickettsiaceae) Detected in Ticks of the Amblyomma maculatum (Acari: Ixodidae) Group Collected from Multiple Locations in Southern Arizona. Issue 6 (24th July 2017) - Allerdice, Michelle E J; Beati, Lorenza; Yaglom, Hayley; Lash, R Ryan; Delgado-de la Mora, Jesus; Licona-Enriquez, Jesus D; Delgado-de la Mora, David; Paddock, Christopher D
Abstract: Rickettsia parkeri is an emerging human pathogen transmitted by Amblyomma ticks in predominately tropical and subtropical regions of the western hemisphere. In 2014 and 2015, one confirmed case and one probable case of R. parkeri rickettsiosis were reported from the Pajarita Wilderness Area, a semi-arid mountainous region in southern Arizona. To examine more closely the potential public health risk of R. parkeri in this region, a study was initiated to investigate the pervasiveness of Amblyomma maculatum Koch group ticks in mountainous areas of southern Arizona and to ascertain the infection frequencies of R. parkeri in these ticks. During July 2016, a total of 182 adult ticks were collected and evaluated from the Pajarita Wilderness Area in Santa Cruz County and two additional sites in Cochise and Santa Cruz counties in southern Arizona. DNA of R. parkeri was detected in a total of 44 (24%) of these ticks. DNA of " Candidatus Rickettsia andeanae" and Rickettsia rhipicephali was detected in three (2%) and one (0.5%) of the samples, respectively . These observations corroborate previous collection records and indicate that established populations of A. maculatum group ticks exist in multiple foci in southern Arizona. The high frequency of R. parkeri in these tick populations suggests a public health risk as well as the need to increase education of R. parkeri rickettsiosis for those residing, working in, or visiting this area.